1985
DOI: 10.1002/j.1460-2075.1985.tb03706.x
|View full text |Cite
|
Sign up to set email alerts
|

Electron microscopy of SV40 DNA cross-linked by anti-Z DNA IgG.

Abstract: Electron microscopy has revealed the specific binding of bivalent anti-Z DNA immunoglobulin G (IgG) to different sites on supercoiled Form I SV40 DNA. The anti-Z IgG links together left-handed regions located within individual or on multiple SV40 DNA molecules at the superhelix density obtained upon extraction. Velocity sedimentation, electrophoresis, and electron microscopy all show that two or more Z DNA sites in the SV40 genome can be intermolecularly cross-linked with bivalent IgG into high mol. wt. comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
1

Year Published

1986
1986
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 16 publications
1
19
1
Order By: Relevance
“…The probability of cruciformation is especially high in pA03 DNA, which is a fourth part of the ColEl plasmid carrying its main palindrome of 31 bp (22). The formation of Z-form segments in pBR322 DNA and SV40 DNA has been tackled experimentally in a number of studies (23)(24)(25)(26). The data reported in (23-24) for pBR322 are not characterized by a very high level of accuracy and do not contradict the results of our calculations.…”
contrasting
confidence: 76%
See 1 more Smart Citation
“…The probability of cruciformation is especially high in pA03 DNA, which is a fourth part of the ColEl plasmid carrying its main palindrome of 31 bp (22). The formation of Z-form segments in pBR322 DNA and SV40 DNA has been tackled experimentally in a number of studies (23)(24)(25)(26). The data reported in (23-24) for pBR322 are not characterized by a very high level of accuracy and do not contradict the results of our calculations.…”
contrasting
confidence: 76%
“…This is ruled out by our calculations: an increased probability of the Z conformation is observed only for 2-3 base pairs adjacement to the a region. Nor do our calculations confirm the conclusion made in (25)(26) to the effect that in SV40 DNA the Z form must first of all appear in the region between residues 1 and 400 which contains the SV40 enhancers ( Figure 2). …”
supporting
confidence: 58%
“…Furthermore, dimers, trimers, and other multimers were observed. Previously, we have shown that these multimers are formed by the binding of bivalent anti-Z-DNA IgGs to Z-DNA tracts on individual DNA molecules (3,4,7,8). In contrast, there was no reactivity of form I M13 or pBR322 at their extracted negative superhelical densities with C-6, D-4, or normal rabbit IgGs (Fig.…”
Section: Methodsmentioning
confidence: 84%
“…The question of where Z-DNA is likely to form in naturally occurring DNA sequences has been addressed experimentally by several groups (DiCapua et al, 1983;Nordheim and Rich, 1983;Stockton et al, 1983;Revet et al, 1984; Barton and Raphael, 1985;Hagen et al, 1985;Miller et al, 1983). The approaches used in these studies are conceptually similar; negatively supercoiled closed circular DNA is exposed to antibodies or chemical reagents that show specificity for Z-DNA, and the subsequent binding sites are qualitatively correlated with nearby stretches of purine-pyrimidine alternation.…”
Section: Introductionmentioning
confidence: 99%